Analisis Perilaku Petugas Parkir Tepi Jalan di Kabupaten Sikka dalam Perspektif Etika - Claudius Yosef Mbei; Konstantinus Pati Sanga; Siktania Maria Dilliana (Universitas 45 Surabaya, 2024)
The research aimed to analyze the behavior of on-street parking attendants in Sikka Regency, focusing on their roles as parking attendants managed by the Transportation Office as a source of Local Revenue (PAD). The theory applied in this research was the Theory of Planned Behavior (TPB). This research employed a qualitative descriptive method, with data sourced from both primary and secondary sources. The analysis was conducted on parking revenue through observations and interviews related to behavioral accounting aspects, including attitudes, perceptions, emotions, motivation, and personality. The analytical technique employed the Miles and Huberman analysis method. The findings indicated that the analysis of the behavior of on-street parking attendants in Sikka Regency, managed by the Transportation Office, showed that in terms of behavioral accounting indicators, attitudes, and personality rated as poor, whereas perceptions, emotions, and motivation rated as good. The management of on-street parking revenue in Sikka Regency was lack of optimal supervision, resulting in fluctuating parking revenue.